Graphic design as urban design: towards a theory for analysing graphic objects in urban environments. - Harland, Robert George (2011)
This thesis presents a model for analysing the graphic object as urban object, by considering atypical fields of discourse that contribute to the formation of the object domain. The question: what is graphic design as urban design? directs the research through an epistemological design study comprising: an interrogation of graphic design studio practice and the articulation of graphic design research questions; a review and subsequent development of research strategy, design and method towards the articulation of methodology that reflects the nature of the inquiry; a detailed analysis of five different ways to study and research graphic design as urban design, in geography, language, visual communication, art and design, and urban design. The outcome of the investigation is a model that enables future research in the urban environment to benefit from micro-meso-macrographic analysis.